Lysosphingolipids in ceramide-deficient skin lipid models - Paraskevopoulos, Georgios; Opálka, Lukáš; Kováčik, Andrej; Paraskevopoulou, Anna; Panoutsopoulou, Eleni; Sagrafena, Irene; Pullmannová, Petra; Čáp, Robert; Vávrová, Kateřina (Journal of lipid research, 2025)
Ceramides are key components of the skin's permeability barrier. In atopic dermatitis, pathological hydrolysis of ceramide precursors - glucosylceramides and sphingomyelin - into lysosphingolipids, specifically glucosylsphingosine (GS) and sphingosine-phosphorylcholine (SPC), and free fatty acids (FFAs) has been proposed to contribute to impaired skin barrier function. This study investigated whether replacing ceramides with lysosphingolipids and FFAs in skin lipid barrier models would exacerbate barrier dysfunction. When applied topically to human stratum corneum sheets, SPC and GS increased water loss, decreased electrical impedance, and slightly disordered lipid chains. In lipid models containing isolated human stratum corneum ceramides, reducing ceramides by ≥ 30% significantly increased permeability to four markers, likely due to loss of long-periodicity phase (LPP) lamellae and phase separation within the lipid matrix, as revealed by X-ray diffraction and infrared spectroscopy. However, when the missing ceramides were replaced by lysosphingolipids and FFAs, no further increase in permeability was observed. Conversely, these molecules partially mitigated the negative effects of ceramide deficiency, particularly with 5%-10% SPC, which reduced permeability even compared to control with "healthy" lipid composition. These findings suggest that while ceramide deficiency is a key factor in skin barrier dysfunction, the presence of lysosphingolipids and FFAs does not aggravate lipid structural or functional damage, but may provide partial compensation, raising further questions about the behavior of lyso(sphingo)lipids in rigid multilamellar lipid environments, such as the stratum corneum, that warrant further investigation.
Keywords: ceramidy; fosforylcholin; Lysophospholipids; Phosphorylcholine; Ceramides; biologické modely; Permeability; Fatty Acids, Nonesterified; lidé; lysofosfolipidy; Models, Biological; Sphingosine; Skin; kůže; kyseliny mastné neesterifikované; sfingosin; permeabilita; Humans